The Relationship Between Parental Socioeconomic Status and Toddler Posyandu Attendance in Kareng Lor Probolinggo City - Ayuningtyas, Jayanti Febry; Lestari, Pudji; Ningtyas, Woro Setia; Puspitasari, Dwiyanti (Rifa'Institute, 2025)
Introduction: Nutritional problems among toddlers remain a public health concern in Indonesia, including in Probolinggo City, where inadequate nutritional status and limited monitoring may hinder early intervention. Low attendance at community health posts for toddlers reduces the continuity of growth monitoring. The socioeconomic level of parents is considered one of the factors influencing attendance. Objective: To analyze the relationship between parental socioeconomic status and toddler attendance at community health posts in Kareng Lor, Probolinggo City. Method: This study used an observational analytic design with a quantitative approach and a cross-sectional method. A total of 100 respondents were selected randomly. Data were analyzed using the Chi-Square test and multivariate logistic regression. Result and Discussion: Parents with lower-middle socioeconomic status were entirely inactive in posyandu visits (100%), those with middle socioeconomic status were mostly active (64.5%), and all parents in the upper socioeconomic group were active (100%). Socioeconomic status showed a significant relationship with posyandu attendance (p < 0.05). Multivariate analysis indicated that the father’s occupation (OR = 16.43; p = 0.006) and household asset ownership (OR = 12.47; p = 0.005) were the dominant factors influencing posyandu attendance. Conclusions: Most parents had a middle socioeconomic level, and socioeconomic differences were associated with the activeness of posyandu visits. Father’s occupation and household assets were the key factors linked to higher attendance.